IDIOMATIC EXPRESSION TRANSLATION STRATEGY IN RHONDA BYRNE’S BOOK THE MAGIC - Fitriyah Fitriyah (Language Literacy: Journal of Linguistics, Literature, and Language Teaching, 2020)
One of the problems in translation is idiom. Idiomatic expressions are unique because their structures cannot always be translated literally and even tend to form new meanings. This research aims to analyze the strategy of English idioms translation in Rhonda Byrne’s book The Magic which was translated into Indonesian entitled The Magic by Susi Purwoko and to find out the most dominant strategy used by translator. This research is a qualitative descriptive study. The data are English idioms and their translation in Indonesian. There are 48 data. Those are analyzed based on Baker’s Idiom translation strategies. They are (1) using an idiom of similar meaning and form, (2) using an idiom of similar meaning but dissimilar, (3) Translation by paraphrase. The result shows that there are three strategies of English idioms translation in Rhonda Byrne's book The Magic. They are (1) using an idiom of similar meaning and form (15 %), (2) using an idiom of similar meaning but dissimilar (31 %), (3) Translation by paraphrase (54); and the most dominant strategy is a translation by paraphrase.